Theoretical Poetics of A. A. Potebnia as a Factor in the Contemporary Theory of Literary Work - Астрахан, Наталія Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyzes the main provisions of A. A. Potebni's psycholinguistic concept from the point of view of their relevance for contemporary literary studies in terms of formation and evolution of the theory of literary work. An attempt is being made to analyze the ideas of «Theoretical Poetics» in the context of the main directions of development of the literary thought of the 20th and the beginning of the 21st century, against the background of methodological searches of literary studies. The potential of interdisciplinary interaction, which does not contradict the general philological subordination of scientific creativity of the scientist, is emphasized in the ideas of A. A. Potebnia.Particular attention is paid to the structural analogy of the word – artistic image – a literary work, which becomes the basis of the concept of literary and artistic creativity proposed by scientists. In accordance with this concept, literary and artistic creativity is considered to be an important factor in the development of mankind, the tool of which is speech, and its method is artistic and poetic thinking. The man involved in the process of creativity, appears as a subject opened to the infinity of knowledge going in the space of the word art.